Pain Outcomes Following Endoscopic Microvascular Decompression for Trigeminal Neuralgia Based on Vascular Compression Type - Blue, Rachel; Yang, Andrew I.; Ajmera, Sonia; Spadola, Michael; Howard, Susanna; Saylany, Anissa; Kvint, Svetlana; Harber, Alexander; Daly, Megan; Shekhtman, Emily; Nair, Anjana; Deshpande, Riddhi; Lee, John Y.K. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background Arterial compression of the trigeminal nerve at the root entry zone has been the long-attributed cause of compressive trigeminal neuralgia despite numerous studies reporting distal and/or venous compression. The impact of compression type on patient outcomes has not been fully elucidated.Objective We categorized vascular compression (VC) based on vessel and location of compression to correlate pain outcomes based on compression type.Methods A retrospective video review of 217 patients undergoing endoscopic microvascular decompression for trigeminal neuralgia categorizing VC into five distinct types, proximal arterial compression (VC1), proximal venous compression (VC2), distal arterial compression (VC3), distal venous compression (VC4), and no VC (VC5). VC type was correlated with postoperative pain outcomes at 1 month (n = 179) and last follow-up (mean = 42.9 mo, n = 134).Results At 1 month and longest follow-up, respectively, pain was rated as “much improved” or “very much improved” in 89 69% of patients with VC1, 86.6 and 62.5% of patients with VC2, 100 and 87.5% of patients with VC3, 83 and 62.5% of patients with VC4, and 100 and 100% of patients with VC5. Multivariate analysis demonstrated VC4 as a significant negative of predictor pain outcomes at 1 month, but not longest follow-up, and advanced age as a significant positive predictor.Conclusion The degree of clinical improvement in all types of VC was excellent, but at longest follow-up VC type was not a significant predictor out outcome. However distal venous compression was significantly associated with worse outcomes at 1 month.
Keywords: vascular compression; trigeminal neuralgia; microvascular decompression; endoscopic; arterial compression; venous compression